Pengembangan Modul Pembelajaran Biologi Cacing Nyale untuk Guru dan Siswa - Imam Bachtiar; Baiq Sri Handayani; Lalu Japa; Syamsul Bahri (Postgraduate, University of Mataram, 2022)
Despite a long tradition of harvesting nyale in southern coast of Lombok island teacher’s understanding on the animal producing nyale are very low. This study aimed to develop a learning module of nyale worm biology for teachers and students. The developmental research method was adapted from the Borg and Gall model which includes 10 steps. Data on module feasibility were collected through a process of validation of the learning module. Questionnaires on the student’s and teacher’s responses to the learning module were administered to assess module practicability. The data were analyzed using descriptive statistics. The results showed that the feasibility of the subject material was 85.90%, the media feasibility was 81.71%, and the user test was 81.09%. The learning module of nyale worm biology is very valid, effective, and practical as a supporting book for learning biology at high schools